Dislocation Generation in Experimentally Shocked Olivine Crystals. Issue 6 (14th June 2022) - Tielke, Jacob A.; Peslier, Anne H.; Christoffersen, Roy; Erickson, Timmons M.; Cline, Christopher J.; Jakubek, Ryan S.; Cintala, Mark J.; Rahman, Zia; Fries, Marc D.; Bouilhol, Pierre
Abstract: During shock metamorphism, crystals in planetary bodies are exposed to extreme conditions of stress, pressure, and temperature, resulting in the development of a range of shock‐induced defects, including dislocations. To investigate the shock‐induced development of dislocations in olivine, one of the most common minerals found in meteorites and other planetary samples, a series of shock experiments were carried out on olivine single crystals. Olivine crystals were shocked to peak reverberation pressures ranging from 21.3 to 58.7 GPa in a flat‐plate accelerator. The crystals were characterized using electron backscatter diffraction (EBSD), Raman spectroscopy, transmission electron microscopy (TEM), Fourier transform infrared spectroscopy, and electron microprobe. EBSD analyses reveal that geometrically necessary dislocations form on all common slip systems. Raman spectroscopy reveals that the full width at half height of characteristic peaks increases linearly as a function of shock pressure. Dislocation loops with the Burgers vector b  = [001] have higher densities near fractures as revealed by TEM analyses, whereas dislocations away from fractures are more dependent on the crystal orientation relative to impact direction. The type and density of dislocations that form during shock are largely independent of the starting hydrogen content of crystals. Calculations that incorporate post‐shock cooling rates of meteorites ejected from planetary surfaces, dislocation annihilation rates in olivine, and dislocation densities measured in shocked olivine suggest that shock‐induced dislocations are preserved in olivine in meteorites ejected from planetary bodies and therefore give insight into the conditions of ancient impact events in the solar system. Plain Language Summary: Most of the crystals in the solar system, including those found on the moon, mars, and asteroids, have been subject to impact events, which send shock waves through the rocks and produce extreme conditions of temperature, pressure, and stress. These shock events may change the physical and chemical properties of the rocks and introduce defects in their crystal structure. We performed a series of experiments to understand how dislocations, which are line defects in crystals, form during shock. We found that the density of dislocations estimated using electron microscopy and the width of peaks in Raman spectra both increase with increasing shock in laboratory experiments. These results may be used to gain insight into the nature of past shock and impact events that occurred in our solar system. Key Points: Olivine crystals were experimentally shocked to produce dislocations Dislocation densities are sensitive to crystallographic orientation with respect to shock wave propagation Dislocations cause the peak width in Raman spectra to increase with increasing shock pressure